K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

8 tháng 7 2017

1/2x+x-2=-3/4

(1/2+1)x=-3/4+2

   3/2x=5/4

       x=(5/4)/(3/2)

       x=5/6

         

23 tháng 9 2021

\(a,\Leftrightarrow x^3-8-x\left(x^2-9\right)=1\\ \Leftrightarrow x^3-8-x^3+9x=1\\ \Leftrightarrow9x=9\Leftrightarrow x=1\\ b,\Leftrightarrow8x^3+12x^2+6x+1-8x^3 +12x^2-6x+1-24x^2+24x-1=0\Leftrightarrow1=0\Leftrightarrow x\in\varnothing\)

23 tháng 9 2021

a) \(\Leftrightarrow x^3-8-x^3+9x=1\)

\(\Leftrightarrow9x=9\Leftrightarrow x=1\)

b) \(\Leftrightarrow8x^3+12x^2+6x+1-8x^3+12x^2-6x+1-24x^2+24x-6=5\)

\(\Leftrightarrow24x=9\Leftrightarrow x=\dfrac{3}{8}\)

2 tháng 2 2023

a) \(\dfrac{x}{3}=\dfrac{4}{12}\Rightarrow x=\dfrac{4}{12}\cdot3=\dfrac{12}{12}=1\)

b) \(\dfrac{x-1}{x-2}=\dfrac{3}{5}\) (Điều kiện : \(x\ne2\))

\(\Rightarrow5\left(x-1\right)=3\left(x-2\right)\)

\(\Leftrightarrow5x-5=3x-6\Leftrightarrow5x-3x=-6+5\Leftrightarrow2x=-1\Leftrightarrow x=-\dfrac{1}{2}\)

c) \(2x:6=\dfrac{1}{4}\Leftrightarrow2x=\dfrac{1}{4}\cdot6=\dfrac{6}{4}=\dfrac{3}{2}\Leftrightarrow x=\dfrac{3}{2}:2=\dfrac{3}{2}\cdot\dfrac{1}{2}=\dfrac{3}{4}\)

d) \(\dfrac{x^2+x}{2x^2+1}=\dfrac{1}{2}\)

\(\Rightarrow2\left(x^2+x\right)=2x^2+1\)

\(\Leftrightarrow2x^2+2x=2x^2+1\)

\(\Leftrightarrow2x^2+2x-2x^2=1\Leftrightarrow2x=1\Leftrightarrow x=\dfrac{1}{2}\).

AH
Akai Haruma
Giáo viên
20 tháng 10 2024

a/

$(2x-3\frac{1}{2})+250\text{%}=6,2$

$(2x-\frac{7}{2})+2,5=6,2$

$2x-\frac{7}{2}=6,2-2,5=3,7$

$2x=3,7+\frac{7}{2}=7,2$

$x=7,2:2=3,6$

AH
Akai Haruma
Giáo viên
20 tháng 10 2024

b/

$(25\text{%}-4\frac{1}{2}x)-2\frac{1}{2}.4^2=5,25$

$(0,25-\frac{9}{2}x)-40=5,25$

$0,25-\frac{9}{2}x=45,25$

$\frac{9}{2}x=0,25-45,25=-45$

$x=-45:\frac{9}{2}=-10$

PT \(\Rightarrow2x^2+2x-3x-6=2x^2-x+4x-8-2\)

\(\Rightarrow-4x=-4\) \(\Leftrightarrow x=1\)

Vậy \(x=1\)

Ta có: \(2x\left(x+1\right)-3\left(x+2\right)=x\left(2x-1\right)+4\left(x-2\right)-2\)

\(\Leftrightarrow2x^2+2x-3x-6=2x^2-x+4x-8-2\)

\(\Leftrightarrow2x^2-x-6=2x^2+3x-10\)

\(\Leftrightarrow2x^2-x-6-2x^2-3x+10=0\)

\(\Leftrightarrow-4x+4=0\)

\(\Leftrightarrow-4x=-4\)

hay x=1

Vậy: x=1